2013
DOI: 10.1021/bi400433b
|View full text |Cite
|
Sign up to set email alerts
|

Autoinhibition and Phosphorylation-Induced Activation of Phospholipase C-γ Isozymes

Abstract: Multiple extracellular stimuli, such as growth factors and antigens, initiate signaling cascades through tyrosine phosphorylation and activation of phospholipase C (PLC)-γ isozymes. Like most other PLCs, PLC-γ1 is basally auto-inhibited by its X-Y linker, which separates the X-and Y-boxes of the catalytic core. The C-terminal SH2 (cSH2) domain within the X-Y linker is the critical determinant for auto-inhibition of phospholipase activity. Release of auto-inhibition requires an intramolecular interaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 44 publications
(98 reference statements)
6
48
0
Order By: Relevance
“…1b). We further confirmed this interaction with PLC-γ1 harbouring the point mutations E347K (in the X catalytic domain), Y747/R748E (in the cSH2 domain) and D1019K (in the Y catalytic domain), all of which disrupt the interaction between the TIM-barrel domain and the cSH2 domain13, and found that all these mutations enhanced the interaction (Fig. 1c).…”
Section: Resultssupporting
confidence: 65%
“…1b). We further confirmed this interaction with PLC-γ1 harbouring the point mutations E347K (in the X catalytic domain), Y747/R748E (in the cSH2 domain) and D1019K (in the Y catalytic domain), all of which disrupt the interaction between the TIM-barrel domain and the cSH2 domain13, and found that all these mutations enhanced the interaction (Fig. 1c).…”
Section: Resultssupporting
confidence: 65%
“…For example, phosphorylation of a conserved tyrosine in the C-terminal tail of FGFRs creates a docking site for Phospholipase Cγ1 (PLCγ1), a tandem SH2-containing substrate (Eswarakumar et al, 2005; Mohammadi et al, 1991; Peters et al, 1992). This recruitment plays a dual role in the activation of the PLCγ pathway: 1) it facilitates phosphorylation of PLCγ which relieves PLCγ autoinhibition, resulting in upregulation of the lipase activity of the enzyme (Bunney et al, 2012b; Hajicek et al, 2013; Poulin et al, 2005), 2) it translocates PLCγ to the vicinity of its substrate phosphatidylinositol 4,5-bisphosphate (PIP2) in the plasma membrane, where the activated enzyme can hydrolyze PIP2 leading to the generation of the second messengers DAG and IP3 (Ellis et al, 1998; Schlessinger, 1997). …”
Section: Introductionmentioning
confidence: 99%
“…These conformational changes away from the autoinhibited form of PLCγ1 would predispose the PLCγ1 molecule for efficient phosphorylation by ITK. Once PLCγ1 is phosphorylated, an intramolecular interaction between pY783 and SH2C (31, 32) can compete with the PLCγ1 SH2C/SLP-76 pY173 interaction and displace PLCγ1 from the SLP-76/ITK signaling complex allowing another round of ITK mediated catalysis to proceed (Fig. 7c).…”
Section: Discussionmentioning
confidence: 99%